Prophetic rage: a postcolonial theology of liberation - Hill, Johnny Bernard (Prophetic Christianity, 2013)
Black religion and nihilism -- Empire and black suffering -- Resistance, rage, and revolution -- Profits versus prophets -- Dark waters -- No ways tired -- Building the world house